[Comment] Quantitative evaluation of colon perfusion after high versus low ligation in rectal surgery by indocyanine green:a pilot study - Li Laiyuan; Du Binbin (结直肠肛门外科)
[Background] In the field of rectal cancer surgery, there remains ongoing debate on the merits of high ligation (HL) and low ligation (LL) of the inferior mesenteric artery (IMA) in terms of perfusion and anastomosis leakage. Recently, infrared fluorescence of indocyanine green (ICG) imaging has been used to evaluate perfusion status during colorectal surgery. [Objective] The purpose of this study is to compare the changes in perfusion status between HL and LL through quantitative evaluation of ICG. [Methods] Patients with rectosigmoid or rectal cancer were randomized into a high or LL group. ICG was injected before and after IMA ligation, and region of interest (ROI) values were measured by an image analysis program (HSL video©). [Results] From February to July 2020, 22 patients were enrolled, and 11 patients were assigned to each group. Basic demographics were similar between the two groups, except for albumin level and cardiac ejection fraction. There were no significant differences in F_max between the two groups, but T_max was significantly higher and Slope_max was significantly lower in the HL group than in the LL group. Anastomosis leakage was significantly associated with neoadjuvant chemoradiation and F_max. [Conclusion] After IMA ligation, T_max increased and Slope_max decreased significantly in the HL group. However, the intensity of perfusion status (F_max) did not change according to the level of IMA ligation.